REVITALISASI KEARIFAN LOKAL TENTANG MATA AIR BAGI SISWA SMA KRISTEN WAIBAKUL, KABUPATEN SUMBA TENGAH, NUSA TENGGARA TIMUR - LASMAN, Diah Kartini (UI Scholars Hub, 2025)
Springs are a natural resource with significant ecological and cultural value for the people of Central Sumba Regency, particularly within the Marapu belief system. However, modernization and environmental changes threaten their sustainability. To revive local wisdom related to springs, the Community Service Team of FIB UI conducted a revitalization program at SMA Kristen Waibakul, Central Sumba. One of the main activities was an art competition themed